Perceived work environment and job satisfaction among public administration employees - Bojadjiev, Marjan; Stefanovska Petkovska, Miodraga; Tomovska Misoska, Ana; Stojanovska, Julijana (The European Journal of Applied Economics, 2015)
This study examines the effects of the percieved work environment on public employee feelings of job satisfaction. Moreover, the paper will investigate the relationship between personal and job characteristics and job satisfaction. The data was collected from a sample of 169 employees working in one local government municipality in Macedonia. The results show that organizational climate and its components significantly predict job satisfaction among public administration employees. The results highlight that employee age acts as the most powerfull predictor of job satisfaction. The analysis of the perceived work environment suggests that recognition is a significant predictor of job satisfaction among public administration employees, followed by opportunities for professional advancement and work itself. The significance of this research lies in its contribution to the knowledge and understanding of determinants that could improve job satisfaction among public administration employees in developing economies.